Use of non-chemical methods for the management of southern blight disease of carrot incited by Sclerotium rolfsii - Rubayet, M. Tanbir; Prodhan, Farhana; Hossain, M. Shamim; Ahmed, Minhaz; Mamun, M. Abdullah Al; Bhuiyan, M. Khurshed Alam (Future Science, 2020)
This experiment was conducted to assess the effect of Trichoderma harzianum, soil solarization, and biofumigant on southern blight dis-ease of carrot incited by Sclerotium rolfsii isolate CS 5. A series of in-vitro and in-vivo trials laid out to select a virulent isolate of S. rolfsii against the carrot variety New Kuroda and evaluated the mustard, cabbage, cauliflower, and broccoli leaf extracts for choosing an effec-tive biofumigant against test pathogen. Mustard was the most effec-tive in inhibiting the radial growth, and sclerotia formation (80.37 and 83.37%) of S. rolfsii (isolate CS 5) at 40% level of concentration followed by cabbage leaf extract (62.22 and 68.69%). On the contrary, a total of 10 isolates of T. harzianum were screened against the test pathogen on Potato Dextrose Agar (PDA) medium for choosing a dominant isolate of T. harzianum. The isolate Th-6 was found as the most active in inhibiting the radial growth (84.44%) of S. rolfsii fol-lowed by Th-1 (75.56%). In the application of T. harzianum, biofumi-gation, and soil solarization, the treatment appeared to be the most superior in reducing pre- and post-emergence mortality of carrot during secondary field trials. The lowest southern blight disease inci-dence (10.77%), and disease severity (12.78%) were found at the same treatment. Subsequently, the yield of carrot was increased 155.18% which might be due to the reduction of carrot disease as well as the addition of organic materials in the soil.